PENGEMBANGAN WISATA TREKKING DI KAWASAN DANAU BUYAN, DESA PANCASARI, KABUPATEN BULELENG - Budayasa, I Ketut (Jurnal Master Pariwisata (JUMPA), 2016)
Buleleng regency in North Bali has many areas that could potentially be developed into tourist destination areas, one of them being Lake Buyan Forest Area which is very potential to be a trekking tour as an alternative form of tourist attraction offering new experiences to tourists. The study was aimed at determining the potential of the forest area as a place for trekking activities, community participation and tourists in the development of the area, and to identify the effective strategies in its development. Data collection techniques used in this study were observation, structured interviews with tourists who were conducting trekking activities and in-depth interview with the related people and the tourists visiting Lake Buyan. The research method used was descriptive-qualitative and SWOT analyses. The study results showed that the physical and non-physical potential owned by forest area of Buyan Lake could be developed into a tourist trekking area, which was also supported by the SWOT analysis. In the process its development, the participation of the related people was an important factor.
Keywords: trekking tourism development; participation; sustainable tourism